A hypothesis-based approach to species identification in the fossil record: a papionin case study - Brasil, Marianne F.; Monson, Tesla A.; Stratford, Dominic J.; Hlusko, Leslea J. (Frontiers in Ecology and Evolution, 2025)
Modern papionin monkeys are a diverse group that encompasses a broad range of morphologies, behaviors, and ecologies. A fossil genus known from African Plio-Pleistocene deposits, Parapapio, is widely regarded as a candidate ancestor to later African papionins. However, despite general agreement that this genus sits at or near the base of the African papionin clade, the taxonomy within Parapapio remains highly contentious. This project evaluates the species-level taxonomy of Parapapio with an explicit hypothesis-based approach to interpreting morphological variation in this sample of fossils. We tested two hypotheses: (H1) the craniodental variation within Parapapio does not cluster into three groups that reflect the three known species, and (H2) all the Parapapio fossils can be accommodated within the craniodental shape and size variation observed for a single extant species of papionin. To test the first hypothesis, we assessed a subset of relatively complete and well-preserved Parapapio crania (n=16), intentionally without reference to previous taxonomic identifications. Specimens were sorted by similarity in cranial features and results were then compared with published taxonomic classifications. Our results demonstrate that morphological traits do not cluster consistently according to the current species categories within Parapapio, failing to reject our first hypothesis. To test our second hypothesis, we examined variation in cranial and dental metrics within Parapapio (n=64) relative to three extant papionin samples (n=310). Our results fail to reject the hypothesis that all Parapapio specimens could belong to a single species and suggest that the three-species paradigm does not reflect the anatomical variation of this genus. We recommend subsuming all Parapapio specimens within Parapapio broomi, the species name with taxonomic priority. The results of this hypothesis-testing approach to taxonomy carry substantial implications for the taxonomy of Parapapio, as well as for biochronological and paleoecological studies more generally, including the taxonomy and paleobiology of hominids recovered from these same deposits.